Monitoring Aquaponik dengan Android untuk Meningkatkan Minat Masyarakat dalam Bercocok Tanam di Kecamatan Porong - Dirgantara, Wahyu; Arifuddin, Rahman; Mujahidin, Irfan (University of Merdeka Malang, 2021)
Sidoarjo Regency, especially Porong District, is an area affected by the Lapindo disaster. The disaster resulted in the closure of several industries and many workers who lost their jobs, agricultural land designation, migration of population from Siring Village to Lajuk. The solution offered to overcome this disaster is by farming using aquaponics techniques. Aquaponics is a farming technique that combines plants and fish. This technique is generally used in urban areas or narrow land. To increase people's interest in farming is by utilizing technology that is used daily. By making a monitoring tool on aquaponics and using an Android phone as a monitoring display to monitor the flow of pool water in aquaponics. This monitoring is needed because the water pump that is used to drain the water flow will become clogged with leaves from the plants above it. The results of monitoring proved to be useful and made it easier for aquaponics owners to monitor whether the pool water flow was blocked or the water flow stopped.DOI:Â https://doi.org/10.26905/abdimas.v6i1.5077Â